2021
DOI: 10.1021/acs.jmedchem.1c01088
|View full text |Cite
|
Sign up to set email alerts
|

Rational Remodeling of Atypical Scaffolds for the Design of Photoswitchable Cannabinoid Receptor Tools

Abstract: Azobenzene-embedded photoswitchable ligands are the widely used chemical tools in photopharmacological studies. Current approaches to azobenzene introduction rely mainly on the isosteric replacement of typical azologable groups. However, atypical scaffolds may offer more opportunities for photoswitch remodeling, which are chemically in an overwhelming majority. Herein, we investigate the rational remodeling of atypical scaffolds for azobenzene introduction, as exemplified in the development of photoswitchable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
0
13
0
2
Order By: Relevance
“…Moreover, using one isomer to target a charge-assisted hydrogen bond between a carboxylic acid and an arginine has been recently implemented in photopharmacology . However, targeting a particular interaction with one of the two isomers is still an underexplored approach for reversible photopharmacology. , We designed two compounds, exploring both meta and para substitution on the outer benzene ring (Figure B). We first evaluated our hypothesis computationally, and IFD poses and subsequent MD simulations suggested that compound 11 could engage in the desired salt bridge only in the case of the cis -isomer (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, using one isomer to target a charge-assisted hydrogen bond between a carboxylic acid and an arginine has been recently implemented in photopharmacology . However, targeting a particular interaction with one of the two isomers is still an underexplored approach for reversible photopharmacology. , We designed two compounds, exploring both meta and para substitution on the outer benzene ring (Figure B). We first evaluated our hypothesis computationally, and IFD poses and subsequent MD simulations suggested that compound 11 could engage in the desired salt bridge only in the case of the cis -isomer (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the atypical azologization of an adamantyl group has been reported in the design of a photoswitchable cannabinoid receptor ligand. 24 However, most drugs do not feature cisoid substructures that can be substituted, thus highlighting the need for a strategy with a broader utility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Recently, Tao et al have described the design of azosters derived from the pharmacophoric structure of the CB 2 R antagonist AM10257. 29 Using a rational remodeling approach, they replaced the adamantyl group of the parent compound with an azobenzene moiety, thereby creating a new photoligand with an affinity for CB 2 R in its cis-form more than 40 times higher than its trans-form. These results opened up new possibilities for photoligand design through a novel structureguided approach.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Subsequently, Carreira, Frank, and co-workers described the synthesis of highly selective CB 2 R agonists coupled to fluorescent and photoswitchable moieties. This new class of hybrid photo-ligands has the ability to monitor CB 2 R signaling by controlling calcium release in real time. , Recently, Tao et al have described the design of azosters derived from the pharmacophoric structure of the CB 2 R antagonist AM10257 . Using a rational remodeling approach, they replaced the adamantyl group of the parent compound with an azobenzene moiety, thereby creating a new photoligand with an affinity for CB 2 R in its cis -form more than 40 times higher than its trans -form.…”
Section: Introductionmentioning
confidence: 99%